Pendekatan Tafsir Kontekstual di Era Pasca-Kebenaran: Upaya Menjawab Tantangan Zaman - Miftahur Rohman (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
The post-truth era is characterized by the dominance of personal opinion, emotion, and belief in shaping public perception, often overriding objective facts and truth. This phenomenon presents new challenges for Islamic studies, particularly in understanding and actualizing the message of the Quran amidst the rapid flow of information and disinformation. This article aims to examine the relevance of the contextual interpretation approach as an effort to address the challenges of the post-truth era. This research uses a library research method with a descriptive-analytical approach to various literature discussing contextual interpretation and the post-truth phenomenon. The results of the study indicate that contextual interpretation enables an understanding of the Quran that is more responsive to social and cultural changes and developments in information technology without neglecting the basic principles of Islamic teachings. This approach helps avoid rigid textual interpretations and strengthens the ability of the community to filter information critically and responsibly. Thus, contextual interpretation has a strategic role in maintaining the relevance of the values ​​of the Qur'an while also being an important instrument in building a moderate, inclusive, and truth-oriented religious awareness in the post-truth era